Penggunaan Flag untuk Mengurangi Permasalahan Input yang Tidak Disengaja pada Controller yang Menggunakan Kinect - Viqi Hanada; Wibisono Sukmo Wardhono; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The usage of Kinect to do an input into a computer by reading the movement and gesture of the user have been rising by these years. Kinect have been used alot as an input controller for a Role Playing Game. The usage of Kinect Gesture Recognition as an extended controller on a game named Steel Battalion: Heavy Armor had been getting many responses that the input done using kinect is unstable, that there are some input that unintended by the user happen when the user is doing nothing, and when the user had just done doing an input. limiting the reading of an input that kinect read using flag variable to divide input phase into 3, standby phase, input phase and reset phase, resulting in clearing the problem of unintended input that happened when user is doing nothing and when user had just done doing an input.